Development of madrasah programs based on local potential stem research on the slopes of Mount Muria - Malichatin, Hanik; Prasetyo, Dody Rahayu (Yogyakarta State University, 2024)
As an effort to instill the love of madrasah students for research and optimize the utilization of local potential on the slopes of Mount Muria, it can be done by developing research-based madrasahs. Through the STEM (Science, Technology, Engineering, Mathematic) research-based madrasah program, it is hoped that the community around the madrasah will better understand how to optimize the local potential. The selected service sample was Madrasah Tsanawiyah (MTs) NU Raden Umar Said located on the slopes of Mount Muria. The service method is carried out in three stages, namely the preparation, implementation, and evaluation stages. The results of the dedication obtained 1) pamelo orange peel waste can be used as a basic material for making soap and biobatteries, 2) the students are enthusiastic about learning STEM research, but the skills to use practicum tools are still low, and 3) the madrasah creates an extracurricular STEM research program based on local potential in Mount Muria. Through this activity, MTs NU Raden Umar Sa'id can become a pioneer of research madrassas on Mount Muria. Thus, it is expected to emulate the surrounding madrassahs.